Answer:
(-10,3),(9,0)
Step-by-step explanation:
Answer:
5 81/100
Step-by-step explanation:
Y = -3x + 13
Steps and the graph are on paper
Since the given problem states that the two angles, angle
1 and angle 2 form a linear pair, this means that they form a 180° line, so
that:
measure angle 1 + measure angle 2 = 180°
Since measure of angle 2 is six more than twice the
measure of angle 1, therefore:
measure angle 2 = 2 (measure angle 1) + 6
hence, substituting this into the first equation:
measure angle 1 + 2 (measure angle 1) + 6 = 180
3 (measure angle 1) = 174
measure angle 1 = 58°
Therefore,
measure angle 2 = 2 (measure angle 1) + 6
measure angle 2 = 2 (58°) + 6
<span>measure angle 2 = 122°</span>